2017
DOI: 10.1021/acsami.7b06855
|View full text |Cite
|
Sign up to set email alerts
|

Generalizable, Electroless, Template-Assisted Synthesis and Electrocatalytic Mechanistic Understanding of Perovskite LaNiO3 Nanorods as Viable, Supportless Oxygen Evolution Reaction Catalysts in Alkaline Media

Abstract: The oxygen evolution reaction (OER) is a key reaction for water electrolysis cells and air-powered battery applications. However, conventional metal oxide catalysts, used for high-performing OER, tend to incorporate comparatively expensive and less abundant precious metals such as Ru and Ir, and, moreover, suffer from poor stability. To attempt to mitigate for all of these issues, we have prepared one-dimensional (1D) OER-active perovskite nanorods using a unique, simple, generalizable, and robust method. Sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 74 publications
2
40
0
Order By: Relevance
“…In contrast, the LaNiO 3 * (Figure b) shows an irregular morphology with the larger size of 100–300 nm. Clearly the polyol method has the advantage of synthesizing LaNiO 3 particles in a smaller size with uniform distribution, compared with other synthesis routes . Figure c shows the SEM image of LaNiO 3 ‐NCNTs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the LaNiO 3 * (Figure b) shows an irregular morphology with the larger size of 100–300 nm. Clearly the polyol method has the advantage of synthesizing LaNiO 3 particles in a smaller size with uniform distribution, compared with other synthesis routes . Figure c shows the SEM image of LaNiO 3 ‐NCNTs.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, various perovskite ABO 3 materials (e.g., LaNiO 3 , LaCoO 3 , etc.) have been synthesized and tested for OER in the last few years . However, large bulk particles are the typical existence form of perovskite oxides that lack a large portion of active sites on surface.…”
Section: Introductionmentioning
confidence: 99%
“…It showed high catalytic activity and outstanding stability in 0.1 m KOH (an onset potential of 1.56 V and Tafel slope of 76 mV dec −1 ). Wong's group synthesized “high aspect ratio” motifs of pure LaNiO 3 perovskite nanorods towards OER for the first time by a template method . Coupled with high surface area, good conductivity and monodisperse morphology, LaNiO 3 provided a great deal of advantages for water oxidation catalysis.…”
Section: Other Ni‐based Oxidesmentioning
confidence: 99%
“…Wong'sg roup synthesized "high aspect ratio" motifs of pure LaNiO 3 perovskite nanorods towards OER for the first time by a templatem ethod. [51] Coupled with highs urface area, good conductivity and monodisperse morphology, LaNiO 3 provided ag reat deal of advantages for water oxidation catalysis. Still, more comprehensive study involving in situ techniquesa nd theoretical calculations is anticipated for developing Ni-based perovskites electrocatalysts for OER.…”
Section: Other Ni-based Oxidesmentioning
confidence: 99%
“…Indeed, ferroelectric ABO 3 perovskite-type oxides, with ag eneral formula of ABO 3 , are noteworthy fort heir advantageous dielectric, piezoelectric, electrostrictive, pyroelectric, and electro-optic properties with corresponding applicationsi nt he electronics industry for transducers, actuators, and high-k dielectrics. [1] In addition, it has been reported that perovskites can be appliedt owards a number of energy-related device configurations, including but not limited to fuel cells, solar cells, and metal-air batteries. [2] In at ypical perovskite structure, the B-site cation is positioned in octahedral coordination with adjacent oxygen atoms, and the A-site cation maintains ac orresponding dodecahedral coordination.…”
Section: Introductionmentioning
confidence: 99%